Depression and suicidal behavior among adolescents living with HIV in Botswana: a cross-sectional study - Anthony A. Olashore; Saeeda Paruk; Ontibile Tshume; Bonginkosi Chiliza (BMC, 2022)
Abstract Background Depression and suicidal behavior are the main causes of disability and morbidity, especially in adolescents living with HIV (ALWHIV). Data regarding these are lacking in Botswana, a country with a predominantly youthful population and ranked among the top four in the world most affected by HIV. Therefore, the present study aimed to estimate the prevalence of depression and suicidal behavior and explore their associated factors in Botswana ALWHIV. Methods Responses were obtained from 622 ALWHIV using the DSM-5 and the Mini-International Neuropsychiatric Interview for Children and Adolescents. Results The mean age (SD) of the participants was 17.7 (1.60) years and more males (54.3%) participated than females. Depression and suicidal behavior rates among adolescents were 23% and 18.9%, respectively. Female participants were more likely to be depressed (AOR = 1.96; 95% CI 1.11-3.45) and have suicidal behaviour (AOR = 6.60; 95% CI 3.19-13.7). Loss of mother (AOR = 2.87; 95% CI 1.08-7.62) and viral load of 400 copies and above (AOR = 5.01; 95% CI 2.86-8.78) were associated with depression. Alcohol use disorder (AOR = 3.82; 95% CI 1.83-7.96) and negative feelings about status (AOR = 8.79; 95% CI 4.62-16.7) were associated with suicidal behavior. Good support (AOR = 0.42; 95% CI 0.23-0.76) and increased frequency of religious activities were protective (AOR = 0.33; 95% CI 0.14-0.79) against depression and suicidal behaviour, respectively. Conclusion Therefore, routine psychologic screening, which includes identifying psychological stressors and maladaptive coping, family and caregiver support services, and psychosocial support platforms, should be integrated into the management package for ALWHIV in Botswana.